Key Issues in Information Systems Management - Brancheau, James C.; Wetherbe, James C. (MIS Quarterly, 1987)
The results from a five-part Delphi survey of chief IS executives and corporate general managers indicate the most critical information systems management issues and consensus on their importance. The research project is the second in a series of such studies conducted by the Society for Information Management and the MIS Research Center at the University of Minnesota. The research confirmed the expected in some areas and revealed surprises in other areas. While strategic planning continued to top all issues in importance, many changes have occurred since 1983. Three new issues have joined the top ten issues in importance. Also, the rank order of several issues in the top ten has shifted. Survey results are discussed in terms of the differing views of IS executives and corporate general managers. A review of how these views have changed over time is also presented. A number of conclusions are drawn about managing information systems and about the changing nature of the IS executive’s job.